Prevalence of ROS1 fusion in Chinese patients with non‐small cell lung cancer. Issue 1 (23rd November 2018) - Zhang, Qing; Wu, Chunyan; Ding, Wei; Zhang, Zhihong; Qiu, Xueshan; Mu, Dianbin; Zhang, Haiqing; Xi, Yanfeng; Zhou, Jianhua; Ma, Liheng; Fu, Shijun; Gao, Min; et al.
Abstract : Background: The study was conducted to investigate the clinicopathological features and prevalence of ROS1 gene fusion in Chinese patients with non‐small cell lung cancer (NSCLC). Methods: The presence of ROS1 fusion was assessed by quantitative real‐time PCR. Associations between ROS1 fusion and clinical characteristics were analyzed. Results: In total, 6066 patients with pathologically confirmed NSCLC and ROS1 fusion test results were enrolled. The average age was 60.89 ± 10.60 years and fusion was detected in 157 (2.59%) patients. Fusion frequency was significantly correlated with age, gender, smoking status (all P < 0.001), pathology type ( P = 0.017), and lymph node metastasis stage ( P = 0.027). ROS1 fusion‐positive patients were significantly younger (55.68 ± 11.34 vs. negative 61.02 ± 10.44 years; P < 0.01). Fusion frequency was higher in women (3.71% vs. men 1.81%), never‐smokers (3.33% vs. smokers 1.21%), and patients with adenocarcinoma (2.77% vs. squamous lung cancer 0.93%) and at advanced node stages (1.31%, 1.40%, 2.07%, and 3.23% for N0, N1, N2, and N3, respectively). No significant correlation between ROS1 fusion status and pathological stage was found in subgroups classified by pathological, tumor, or metastasis stage ( P > 0.05). Age, smoking status, and lymph node stage were statistically significantly correlated with ROS1 fusion frequency (all P < 0.05); gender and pathology type were not significantly correlated with ROS1 fusion status after adjusting for smoking status. Conclusion: An overall ROS1 fusion frequency of 2.59% was confirmed in this study. ROS1 fusion was more prevalent among younger patients, never‐smokers, and those at advanced node stages.